Bravehearts - Moe, Kari Anne (Norway, 2012)
Over the period of a year, the film followed the lives of four active students from different Norwegian political parties who decided to stand in student elections. However, in midsummer 2011, the stories of Johanne, Haakon, Sana and Henrik are impacted by the self-styled “defender of European traditions” Anders Breivik, who murdered dozens of young members of the Norwegian Labour Party on the island of Utøya. His horrific act, fuelled by years of frustration with Norwegian society’s multicultural direction and bolstered by a hatred of Muslims, rocked the country. One of those who narrowly escaped the rampaging murderer was Johanne. Like the whole of Norway, she finds coming to terms with the shocking experience immensely difficult.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films